2010
DOI: 10.1016/j.jim.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Serum, plasma, and dried blood spot high-sensitivity C-reactive protein enzyme immunoassay for population research

Abstract: C-reactive protein (CRP) is used as a biomarker of morbidity and mortality risk in studies of population health, and is essential to interpretation of several micronutrient biomarkers. There is thus need for a robust high sensitivity CRP (hsCRP) measurement method for large-scale, nonclinical studies. We developed an efficient, inexpensive assay suitable for quantifying CRP across the physiological range using any blood specimen type. The ELISA uses readily available monoclonal antibodies to measure CRP in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 28 publications
(34 reference statements)
5
121
0
Order By: Relevance
“…CRP was measured using a particle enhanced immunonepholometric assay (BNII nephelometer from Dade Behring Inc., Deerfield, IL) at the University of Vermont (Ryff et al, 2013). CRP measured from blood spots are highly correlated with CRP measured from serum (e.g., Brindle et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…CRP was measured using a particle enhanced immunonepholometric assay (BNII nephelometer from Dade Behring Inc., Deerfield, IL) at the University of Vermont (Ryff et al, 2013). CRP measured from blood spots are highly correlated with CRP measured from serum (e.g., Brindle et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Serum was collected and stored at -80°C until it could be analyzed as a batch, to avoid interassay variability. Samples were stored for up to 10 months (CRP concentrations reportedly remain stable in serum stored at -20°C for up to a year in a controlled laboratory setting and up to 34 months in a research setting 28 ). The CRP concentrations were measured with an automated turbidimetric immunoassay for human CRP d,e previously validated for use in dogs.…”
Section: Small Animals/ Exoticmentioning
confidence: 99%
“…These drying measures decrease sample weight by >90%, thus decreasing transport burden, and in theory can enhance long-term sample stability by decreasing water-dependent analyte degradation caused by hydrolysis and enzyme activity (12). Unfortunately, DBS stored in challenging environments (i.e., elevated temperatures and humidity) quickly lose their protective capacity (13,14). Indeed, years of field research supported by the Centers for Disease Control has shown that DBS on-card drying approaches do not fully safeguard all blood analytes (15).…”
mentioning
confidence: 99%